Fixed drug eruptions with intraoral presentation - Srivastava, Rahul (Indian J Dent, 2015)
Fixed-drug eruption (FDE) is an unusual and rare adverse drug reaction. This type of reaction is actually a delayed type of hypersensitivity reaction that occurs as lesions recurring at the same skin site due to repeated intake of an offending drug. Here is a case report of a 58-year-old male patient who developed intraoral FDEs after ingestion of the first dose of ornidazole.